Análise de vibração de eixos em bombas hidráulicas centrífugas - Oliveira, Filipe Holmann (2017)
The use of shafts is essential for most of the machines, which can transmit torque for the local where it is necessary. An unbalanced shaft influences a lot the performance of the machine, and can be unsafe for people around, specially when occurs the ressonance or harmonics at the components. So, it is very importante the shafts being very well balanced, avoiding any accident. Unfortunatelly, it doesn’t exist a perfect balancing in real systems, being necessary achieve the acceptable unbalance, indicated by tecnichal standard ABNT NBR 8008.